2014
DOI: 10.1111/1744-7917.12095
|View full text |Cite
|
Sign up to set email alerts
|

Application of DNA barcoding to the identification of Hymenoptera parasitoids from the soybean aphid (Aphis glycines) in China

Abstract: Aphis glycines Matsumura is an important pest of soybean in Asia and North America. Hymenoptera parasitoids play a key role in the control of the soybean aphid. The correct identification of parasitoids is a critical step that precedes the assessment of their potential biological control agents. Accurate identification of the majority of the species attacking the soybean aphid often requires elaborate specimen preparation and expert taxonomic knowledge. In this study, we facilitated the identification of soybe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
2
14
1
Order By: Relevance
“…This fragment is longer than the standard DNA barcode region proposed by Hebert et al (2003) for fauna and overlaps in 365 bp with that standard region. Regarding the variability of this fragment, the average intraspecific divergence was low (0.12%) with respect to results reported for other insect groups: 0.36% for aphid parasitoids (Hymenoptera) in China (Zhou et al, 2014), 0.80% for species of the genus Spodoptera of Lepidoptera in Florida (USA) (Nagoshi et al, 2011), 1.39% for the genus Epitrix (Coleoptera) in Europe and North America (Germain et al, 2013), 1.60% in sandfly species (Diptera) in Colombia (Contreras Gutiérrez et al, 2014), and 3.14% for aphid species of the genus Toxoptera (Hemiptera) in China (Wang & Qiao, 2009). This expected low intraspecific variability may be explained by the restricted geographic area included in the present study (corn production area of central Argentina).…”
Section: Discussioncontrasting
confidence: 69%
“…This fragment is longer than the standard DNA barcode region proposed by Hebert et al (2003) for fauna and overlaps in 365 bp with that standard region. Regarding the variability of this fragment, the average intraspecific divergence was low (0.12%) with respect to results reported for other insect groups: 0.36% for aphid parasitoids (Hymenoptera) in China (Zhou et al, 2014), 0.80% for species of the genus Spodoptera of Lepidoptera in Florida (USA) (Nagoshi et al, 2011), 1.39% for the genus Epitrix (Coleoptera) in Europe and North America (Germain et al, 2013), 1.60% in sandfly species (Diptera) in Colombia (Contreras Gutiérrez et al, 2014), and 3.14% for aphid species of the genus Toxoptera (Hemiptera) in China (Wang & Qiao, 2009). This expected low intraspecific variability may be explained by the restricted geographic area included in the present study (corn production area of central Argentina).…”
Section: Discussioncontrasting
confidence: 69%
“…This indicated that the 28S is not appropriate marker to separate these two species. Derocles et al (2011) and Zhou et al (2014) also demonstrated that these species were very closely related and that the 28S gene was unable to differentiate them.…”
Section: Discussionmentioning
confidence: 99%
“…Even when keys are available, they are difficult to use and morphological identification of species remains problematic if not impossible for non-specialists (Tomanovic et al 2003). Consequently, misidentification of parasitoids used in biocontrol may result in serious economic losses (Compere 1961;Rosen & Debach 1973;Zhou et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Using the DNA barcoding technique, Zhou et al . () identify 15 Hymenoptera parasitoid species belonging to 10 genera of five families from the soybean aphid populations in northeastern China. Xu et al .…”
mentioning
confidence: 99%
“…Their results indicate that soybean aphids are recovered in suction traps about 2 weeks earlier than in traditional field surveys, indicating the efficiency of suction traps in aphid monitoring. Using the DNA barcoding technique, Zhou et al (2014) identify 15 Hymenoptera parasitoid species belonging to 10 genera of five families from the soybean aphid populations in northeastern China. Xu et al (2014) report an interesting finding that the cucurbit-specialized lineages of A. gossypii have the potential to utilize mature or whitefly-stressed cotton plants as temporary hosts.…”
mentioning
confidence: 99%